Determinação do teor mássico de blendas binárias de polímeros semicristalinos via DSC: uma nova abordagem matemática - Caetano, Jorge Baes (Universidade Federal de São Carlos, 2025)
This work presents the development and validation of a novel mathematical approach for determining the mass fraction of immiscible binary blends of semicrystalline polymers using differential scanning calorimetry (DSC). Previously studied methods for quantitative analysis of polymer blends typically require prior characterization of the individual components and their mixtures at different proportions, aspects that can limit and increase the cost of their application. The proposed methodology is innovative as it eliminates these requirements, making it particularly relevant in the context of the mechanical recycling of multicomponent plastic packaging. In such cases, recycled polymers are often contaminated with other polymers due to improper separation or the recycling of multilayer packaging composed of more than one polymer. The approach presented here is based on DSC testing, using measurements of the polymers' melting enthalpies in the binary blend. Grounded in the crystallinity degree equation, a mathematical model is derived by filtering a bidimensional set—referred to as the crystallinity set—using boundary conditions. From this reduced set, the possible mass fraction values of the polymers in the blend are calculated, and their average is used to determine the mass content as these values converge to the actual content. To validate the method, seven blends of high-density polyethylene and isotactic polypropylene (HDPE/PP) were prepared with compositions of 5, 20, 40, 50, 60, 80, and 95% (w/w) HDPE using a co-rotating interpenetrating twin-screw extruder. Each polymer mixture was micronized through cryogenic grinding to better represent the nominal mass fraction, and the resulting powder was subjected to DSC testing. The developed mathematical approach was then applied to each sample to determine its respective mass content. Finally, for method validation, these values were compared to the nominal content. The results demonstrated that the method successfully determined the HDPE mass fraction in the HDPE/PP blend. For the blends containing 5%, 20%, 40%, 50%, 60%, 80%, and 95% HDPE by mass, the method determined contents of 4.7%, 21.1%, 40.0%, 43.3%, 55.9%, 76.9%, and 95.7% (w/w), with respective errors of 0.3%, 1.1%, 0%, 6.7%, 4.1%, 3.1%, and 0.7% (w/w) HDPE. This study proposes a promising tool for the quantitative characterization of polymer blends composed of semicrystalline polymers and opens new perspectives for future research in the field.
Determination of the mass content of binary semicrystalline polymer blends via DSC: a new mathematical approach
Keywords: Análise quantitativa; Blendas poliméricas; DSC; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES